2018
DOI: 10.1111/tbj.13050
|View full text |Cite
|
Sign up to set email alerts
|

Radiographically guided shave margins may reduce lumpectomy re-excision rates

Abstract: Minimizing margin re-excision optimizes patient care by providing appropriate oncologic resection and reducing costs. This study aims to assess margin positivity rate in two groups: shave margin based on gross specimen (control group, CG) vs shave margin based on intraoperative imaging (radiographic group, RG). A total of 182 patients who underwent lumpectomy for stage O-III breast cancer at a single institution from January 2013 to January 2014 were evaluated. There was statistically significant decrease in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Otra de las ventajas, y la más importante, es que permite comprobar intraoperatoriamente los márgenes de la lesión y, si es necesario, realizar una ampliación de esos márgenes en ese momento, disminuyendo así el número de reintervenciones por márgenes afectos [36][37][38] . Si, además, asociamos la EIO al estudio de los márgenes ex vivo intraoperatoriamente, tal y como lo realizamos en nuestro hospital, el porcentaje de reintervenciones por márgenes afectos mejora significativamente [39][40] . Ésto conlleva un mejor resultado estético incrementando la satisfacción de los pacientes y su calidad de vida.…”
Section: Discussionunclassified
“…Otra de las ventajas, y la más importante, es que permite comprobar intraoperatoriamente los márgenes de la lesión y, si es necesario, realizar una ampliación de esos márgenes en ese momento, disminuyendo así el número de reintervenciones por márgenes afectos [36][37][38] . Si, además, asociamos la EIO al estudio de los márgenes ex vivo intraoperatoriamente, tal y como lo realizamos en nuestro hospital, el porcentaje de reintervenciones por márgenes afectos mejora significativamente [39][40] . Ésto conlleva un mejor resultado estético incrementando la satisfacción de los pacientes y su calidad de vida.…”
Section: Discussionunclassified
“…SR is a fast, convenient, and cost‐effective method. Several studies demonstrated that intraoperative mammography reduced positive margins 3,4 . No significant difference was found between SR and frozen sectioning 5 .…”
Section: Value 95% Confidence Intervalmentioning
confidence: 99%